Analysis of Employee Engagement as A Variable to Mediate The Influence of Competence and Work Environment on Employee Performance in The Yogyakarta Special Region Transportation Office - Agus Haryadi; Purbudi Wahyuni (AIBPM Publisher, 2022)
ABSTRACTThe purpose of this study was to examine the effect of competence and work environment on employees, as well as the effect of competence and work environment mediated by employee engagement at the Yogyakarta Department of Transportation. The main focus of this research is how the DIY Transportation Service made a new breakthrough to make Yogyakarta traffic flow run and how the DIY Transportation Service work environment is work during the Covid-19 pandemic. Methods of data processing and data analysis in this study use descriptive and quantitative analysis. The population in this study amounted to 58 employees. The sampling technique used was the saturated sample technique which made all employees who collected 58 employees as samples. The analysis technique in this study uses path analysis. The results of this study indicate that competence has a significant positive effect on employee performance. The work environment has no significant positive effect on employee performance. Competence has a significant positive effect on employee performance mediated by employee engagement. The work environment has a significant positive effect on employee performance mediated by employee engagement.Keywords: Employee Engagement, Employee Performance, Work Environment.